Revisiting Neoliberalism in Indonesian Minimarket Marketing Strategies and Financial Reporting: How Do They Perform? - Destiana, Rina; Rawi, Rawi; Muthiarsih, Tiara (Scientechno: Journal of Science and Technology, 2024)
This study analyzes the impact of neoliberalism in minimarket marketing strategies on financial reporting and financial performance in Indonesia, focusing on the case studies of Indomaret and Alfamart. Neoliberalism, with its emphasis on market liberalization and deregulation, has influenced the business model and marketing strategy of minimarkets. This study uses a qualitative approach with descriptive analysis. Data was obtained through in-depth interviews, literature studies, and analysis of financial statements. The results of the study show that marketing strategies influenced by neoliberalism have a significant impact on financial reporting and financial performance of the two minimarkets.